Impact of Protean Career Attitude on Employee Engagement: Evidence from Auditing Firms - Raveendran, T.; Balasubramaniam, K. (South Eastern University of Sri Lanka, 2022)
Protean career has gained particular attention in contemporary career era. Constructs of protean careers have notified career theory for years. Especially in Sri Lankan context the research on protean career attitude is not adequate as per the review of literature. The current study attempts to examine the impact of protean career attitude on employee engagement among the audit service employees in the Northern Province. The scales related to protean career attitudes measure self- directed behavior and values-driven career attitude. For the purpose of this study, 105 employees of audit firms were selected. Regression analysis was employed to test the hypotheses. The results revealed that self- directed behaviour has a positive impact on employee engagement whereas values-driven career attitude doesn’t significantly influence employee engagement. The results of the study give an insight that, to promote employee engagement, managers should facilitate for employees self-directed career behavior.
Keywords: Protean career attitude; Employee engagement; Audit firms